"The Constant State of Becoming": Power, Identity, and Discomfort on the Anti‐Oppressive Learning Journey. Issue 4 (January 2015) - Hart, Andrew; Montague, Jane
<x xml:space="preserve">Abstract</x> The development of a clear personal and professional identity—"knowing oneself"—is frequently cited as a key factor in supporting anti‐oppressive practice. In the field of health and social care, work placements are a major vehicle for equipping students to become anti‐oppressive practitioners committed to making effective diversity interventions in a range of organizational settings. This article highlights some of the tensions inherent in the formation of such an identity and pays particular attention to issues such as discomfort, power inequalities, the discursive production of the self, and ways in which educational and workplace organizational settings can simultaneously promote and inhibit such identity development. The article concludes that the discomfort experienced by students as part of this learning process is not only inevitable but necessary to becoming an anti‐oppressive practitioner and that the narrative process offers ways of empowering both students and service users to challenge oppression.